Evolution of hotspots and research trends in agricultural mulch film research: a bibliometric review - Wang, Kuaishun; Jin, Tuo; Wang, Bei; Yuan, Zheming; Peng, Kewei; Hu, Yuan (Frontiers in Environmental Science, 2024)
Agricultural mulch film (AMF) can increase the soil temperature, reduce the evaporation of water and soil erosion, control the number of weeds and pests, and improve the yield and quality of crops. However, the environmental pollution caused by AMF residues is becoming serious and has attracted increasing amounts of research. Research on AMF is a complex subject with diverse content and rich perspectives. Currently, there have been few systematic reviews of the use of AMF. To comprehensively and deeply understand the current status, hotspots, and trends of research on AMF, this paper conducted a bibliometric analysis of AMF literature from 1960 to 2022. Results are as follows: the overall publication volume in the field of AMF has increased 1960 to 2022. The top three countries contributing to publication volume include China, United States (US) and India United States (US), which are also the main collaborating nations. Notably, cooperation between China and US is the most frequent, and a cluster constituted by Eeuropean nations serve as a primary collaborator for other countries. Owing to the introduction and development of the concept of degradable plastics, the field entered a period of rapid growth after 1970 and has primarily focused on continuous development in the areas of horticulture and environmental science. Current research on AMF primarily aims to: 1) develop applications that are aimed at enhancing the yield and quality of crops, and 2) improve the materials used to produce AMF to reduce its environmental impact. The persistent hotspots of research in AMF revolve around modifying the soil microclimate, promoting crop growth and development, and increasing crop yields. Frontier AMF research includes: exploring crop quality enhancement mechanisms, developing low-cost biodegradable film technologies and their natural degradation effects, and investigating AMF's impact on soil nitrous oxide emissions and associated mechanisms.